Synthesis, characterization and properties for electrochemical energy storage of manganese dioxide - Kang, Jiani (2017)
The nanomaterials are used widely and effectively in electrochemical energy storage because of their advantages, such as nanoscale structures and large surface area to volume ratio. The unique properties of nanomaterials in different aspects are attracting many research interests in recently years. Batteries are one form to store electrical energy which commonly used in our daily lives. Zinc-Manganese as an effective battery cell can be synthesized by different methods. In this battery cell, manganese dioxide (MnO2) is used as cathode to transfer the electrons, to the zinc anode within the electrolyte used. The purpose of this research is to synthesis MnO2 nanomaterials by co-precipitation and hydrothermal methods. For co-precipitation, KMnO4 solution was added into MnCl2 solution to get the precipitate of MnO2. The factor, which is the concentration of KMnO4 solution, would be changed during the experiment to compare the different structures of MnO2 precipitate. For hydrothermal, MnO2 would be grown on carbon cloth by applying the high temperature and pressure for KMnO4 solution. The structure, phase and morphology of MnO2 nanomaterials were measured via scanning electron microscopy (SEM) and X-Ray diffraction (XRD). The cycling performance were investigated by electrochemical workstation and land battery testing system. The nanostructures of MnO2 directly coated on the substrate, carbon cloth, can fasten the ion/electron movement. The MnO2 nanomaterials owe low electrochemical impedance and thus, higher response rate can be expected